Students’ problem-solving ability in number patterns topic viewed from cognitive styles - Sri Rejeki; Luthfi Rahmasari (Universitas Hamzanwadi, 2022)
Mathematical problem-solving skills are essential. However, students’ ability to solve number patterns problems topic has not been optimal. The results of previous studies show different problem-solving skill profiles in students with Field Dependent (FD) and Field Independent (FI) cognitive styles in geometry and algebra. Therefore, this study aims to describe the problem-solving ability of students in number patterns based on cognitive styles. The research used qualitative methods with a descriptive approach. The study involved all students of grade 8 at a public junior high school in Klaten Regency, Central Java, Indonesia. Four students were selected for in-depth analysis by administering the Group Embedded Figure Test (GEFT) test and many patterns problem-solving test. Instruments used in this study included the GEFT test and the problem-solving test of number patterns. Research data was collected through a test, interviews, and documentation. The triangulation was applied to validate the data. Data were processed by reducing data, presenting data, and verifying. The results showed that FI students are better able to solve number pattern problems than FD students. It can be seen that FD students can understand the problem, devise a plan, and carry out the plan. However, FD students have been unable to look back at the solutions. Meanwhile, FI students can understand problems, devise a plan, carry out the plan, and look back at the solutions well. Therefore, it is needed to focus more on enhancing FD students’ ability in the stage of looking back.